The World Financial Crisis and The Polish Economy - Adamowicz, Mieczysław; Adamowicz, Tomasz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2019)
The subject of the work is to provide an overview of the global financial crisis in the years 2007-2011; its course, symptoms and effects in the world and in Poland. The work presents the causes and the sources of crisis as well as corrective measures taken by governments and financial institutions. The subject literature and information from different national and international financial institutions and organisations were used as a source of research materials and data for analysis. The financial crisis appeared in Poland with some delay and was less intensive than in other developed countries. Anti-crisis measures taken in Poland complied with the recommendations of the European Union and the International Monetary Fund. The measures taken by the Polish central bank concerned the institutional sphere, the manner in which the financial policy worked and how it was pursued, as well as the real sphere of the economy, including especially enterprises, households and public institutions.